Synchronous sigmoid and transverse volvulus: A case report and qualitative systematic review. (2020) - Ndong, Abdourahmane; Diao, Mohamed Lamine; Tendeng, Jacques Noel; Diallo, Adja Coumba; Ma Nyemb, Philippe Manyacka; Konaté, Ibrahima
Highlights: Colonic volvulus represents the leading cause of colonic obstruction in sub-Saharan Africa. The sigmoid colon is the primary site of volvulus while the transverse colon is a rare condition. The synchronous occurrence of a sigmoid colon and transverse colon volvulus is exceptional. The dual location of strangulation makes it a major surgical emergency with a high risk of gangrene and septic shock. The literature concerning its description is sparse and the treatment options are poorly codified. Abstract: Introduction: Colonic volvulus is defined as a torsion of a part of the colon causing large bowel obstruction by strangulation which may lead to ischemia and then necrosis. The synchronous occurrence of a sigmoid colon and transverse colon volvulus is exceptional. We describe a case of synchronous sigmoid and transverse volvulus in a patient with a qualitative systematic review of this condition. Presentation of the case: This is a 74-year-old patient with a history of chronic constipation, who consulted for bowel obstruction. Plain abdominal radiography showed diffuse gas distension of the colon with the absence of rectal gas. An exploratory laparotomy was performed and showed sigmoid colon volvulus associated with synchronous transverse colon volvulus without bowel necrosis. A left hemicolectomy with loop colostomy was performed. The restoration of bowel continuity was done 3 weeks. The post-operative course was uneventful. Discussion: The occurrence of a simultaneous sigmoid and transverse colonic volvulus is an exceptional situation. Due to the rarity of this clinical entity, the literature concerning its description is sparse and the treatment options are poorly codified. There are no guidelines in the treatment and a tailored approach should be used for each patient. Conclusion: The dual location of strangulation makes this situation a major surgical emergency with a high risk of gangrene and septic shock. Colectomy with delayed anastomosis should be preferred in the treatment.